2019
DOI: 10.1142/s0219498820501224
|View full text |Cite
|
Sign up to set email alerts
|

On Prüfer-like properties of Leavitt path algebras

Abstract: Prüfer domains and subclasses of integral domains such as Dedekind domains admit characterizations by means of the properties of their ideal lattices. Interestingly, a Leavitt path algebra L, in spite of being noncommutative and possessing plenty of zero divisors, seems to have its ideal lattices possess the characterizing properties of these special domains.In [8] it was shown that the ideals of L satisfy the distributive law, a property of Prüfer domains and that L is a multiplication ring, a property of Ded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…While conditions (2)- (5) in the above definition are generally not interchangeable, they happen to coincide in Leavitt path algebras. Proposition 3.2.…”
Section: Multiplicative Conditions On Idealsmentioning
confidence: 99%
“…While conditions (2)- (5) in the above definition are generally not interchangeable, they happen to coincide in Leavitt path algebras. Proposition 3.2.…”
Section: Multiplicative Conditions On Idealsmentioning
confidence: 99%
“…Upon dropping terms, if needed, we may assume that the intersection is irredundant. If I is non-graded, then, upon further reindexing, Lemma 4.7 (2,4,5) gives that |Y | = n ≤ m for some positive integer n, that for each i ∈ {1, . .…”
Section: Products and Intersections Of Completely Irreducible Idealsmentioning
confidence: 99%
“…In particular, a number of papers have been devoted to characterizing special types of ideals of L in terms of graphical properties of E, and to describing the ideals of L that can be factored into products of ideals of these types. More specifically prime, primitive, semiprime, and irreducible ideals have received such treatment in the literature-see [2,3,4,5,12,14]. An interesting feature of Leavitt path algebras is that, while they are highly noncommutative, multiplication of their ideals is commutative, and further, their ideals share a number of properties with ideals in various commutative rings, such as Dedekind domains (where ideals are projective), Bézout rings (where finitely-generated ideals are principal), arithmetical rings (where the ideal lattices are distributive), and Prüfer domains (where the ideal lattices have special properties).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent paper [7], it has been shown that the ideals of a Leavitt path algebra satisfy two more characterizing properties of Prüfer domains among integral domains.…”
Section: The Lattice Of Ideals Of a Leavitt Path Algebramentioning
confidence: 99%